Geostatistical analysis for temperature monitoring in the State of Bahia, Brazil - Chaves, Michel Eustáquio Dantas; Conceição, Katyanne Viana da; Guerrero, João Vitor Roque (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Climate monitoring is an essential element for predictions of temperature changes and their influence on environmental health and safety. However, the sparse density of meteorological stations limits the collection of reliable data and makes it difficult to analyze climatic variables and events, which makes it necessary to use data estimators where there are no measurements, such as interpolations. The aim of this work was to evaluate which interpolation method best represents the climatic variable of maximum temperature in the State of Bahia, with the use of historical temperature series and a Digital Elevation Model from Shuttle Radar Topographic Mission - SRTM data. As results, we observed that the geostatistical interpolators presented better performance, especially Cokriging, and that the use of geographic information systems are important tools for studies of this subject.